Transcriptome, intestinal microbiome and histomorphology profiling of differences in the response of Chinese sea bass (Lateolabrax maculatus) to Aeromonas hydrophila infection - Pan, Chao; Zhu, Yanran; Cao, Kaixin; Li, Juexian; Wang, Siyu; Zhu, Jiahua; Zeng, Xiaoman; Zhang, Heqian; Qin, Zhiwei (Frontiers in Microbiology, 2023)
The Chinese sea bass (Lateolabrax maculatus) is an important aquaculture fish, but diseases caused by Aeromonas hydrophila have led to severe economic losses to the aquaculture industry in recent years. To date, only a few studies have focused on the relationship between the intestinal immune response and changes in intestinal microbes by A. hydrophila infection. Here, we report the transcriptome and intestinal changes in infected sea bass. Histopathological results showed that severe steatosis and vacuolation occurred in the liver and that the intestinal villi and mesentery were seriously affected after infection. By extracting total RNA from intestinal tissue and studying the transcriptome profile, 1678 genes (1013 upregulated and 665 downregulated) were identified as significantly differentially expressed genes (DEGs). These genes are involved in many immune-related signalling pathways, such as the NOD-like receptor, C-type lectin receptor, and Toll-like receptor signalling pathways. Moreover, the intestinal microbes of sea bass changed significantly after infection. Interestingly, at the genus level, there was an increase in Serratia, Candida arthromitus and Faecalibacterium as well as a decrease in Akkermansia and Parabacteroides after infection. The results also indicated that some of the DEGs involved in the immune response were related to the genus level of intestinal microbiota. Finally, there was a relationship between gene expression patterns and the bacterial structure in the host intestine. Our study provides a reference for the study of the immune response and particular functions of intestinal microbes of sea bass after pathogen infection.